More but Smaller: Marine Heatwaves Exacerbate Size Truncation in Overfished Fish Communities in the Skagerrak - Kjell Magnus Norderhaug; Portia Joy Nillos Kleiven; Thomas Wernberg; Ann‐Elin Synnes; Karen Filbee‐Dexter; Sigurd Espeland; Jonas Thormar; Kyrre Heldal Kartveit; Lene Christensen; Even Moland (Ecology and Evolution)
ABSTRACT As we are progressing through the Anthropocene, it is imperative to understand how ecosystems degraded by historical impacts respond to future pressures. Particular attention should be directed at changes in the distribution and function of foundation species due to their disproportionately important ecological roles. Forest‐forming kelps are in decline and are being replaced by turf‐forming algae in coastal areas globally, as a consequence of increasingly severe marine heatwaves (MHW). This replacement represents a miniaturization of the three‐dimensional habitat and a change in habitat functions for many associated species. Ecologically, economically, and culturally important coastal fish species depend on kelp forests in different life stages from egg to adult and may be affected in various ways. Many of these species already suffer from centuries of overexploitation, severely reducing abundances, truncating sizes, and changing age distributions. Here, we studied an overfished coastal ecosystem and assessed the impact of the transition from kelp to turf on the structure and function of associated fish communities. Specifically, we analyzed differences in abundance, body size, and composition of benthic fish at sites with variable cover of kelp and turf. We found higher abundances of small fish with increasing cover of turf relative to kelp. We also found smaller fish within the common families of gobids and gadids. Thus, MHW exacerbate size truncation and trophic downgrading in coastal fish communities. However, no differences in abundances of fish in the water column were detected during the night, and the average size of fish at turf‐dominated sites was even larger. We interpreted this as roving predatory fish during night‐time being less affected by the shift in habitat and smaller‐bodied prey avoiding the water column in open turf habitats.